FÍSICA PARA TODOS: A EXPERIMENTAÇÃO COMO ELEMENTO DE MOTIVAÇÃO E DE DIFUSÃO DA CIÊNCIA - Bonadiman, Helio; Bonfada, Edenilso; Schwerz, Cristiane; Pianesso, Jordana; Puhl, Rangel; Soldera, Luana (Salão do Conhecimento, 2013)
Resumo